The effect of natural plant-based homogenates as additives on the quality of yogurt: A review. (October 2022) - Fan, Xiankang; Li, Xiefei; Du, Lihui; Li, Jianhao; Xu, Jue; Shi, Zihang; Li, Chunwei; Tu, Maoling; Zeng, Xiaoqun; Wu, Zhen; Pan, Daodong
Abstract: Significant research has been conducted on using natural plant-based homogenates (NPBH) as additives to improve the quality of yogurt. This paper reviews the effects, mechanisms, and research methods of NPBH as additives to the probiotic content, texture, flavor, and nutritional value of yogurt. The mechanisms by which NPBH promotes the growth of lactic acid bacteria are reviewed, including nutrients in the homogenates, a suitable buffering environment, and the metabolic production of probiotics. Fructose, pectin, dietary fiber, protein, and polysaccharides are the primary influences on the yogurt texture. The aromatic precursors contained in NPBH, their contribution to yogurt flavor, and the health benefits of yogurt nutritional fortification are detailed. In the future, priority could be given to adding Chinese herbs (like wolfberry, saffron, and Rhodiola) with preventing alcoholic liver, anti-aging, blood pressure reduction, and other disease treatment or prevention functions to the yogurt to achieve a win-win situation. In addition, research on the function of NPBH yogurt should focus on the clinical implications. Graphical abstract: Graphical abstract Summary of research on plant-based as additives in yogurt. Image 1 Highlights: This paper reviews the effects of NPBH as additives on yogurt. The NPBH as additives on yogurt promote the growth of LAB are reviewed. Pectin etc. in NPBH affect yogurt texture are summarized. A review of aroma precursors contained in NPBH which contribute to yogurt flavor.